Knowledge and practice of hand hygiene among the doctors of Patan Hospital, Nepal - Bhatt, Prashant Raj; Paudel, Ujjawal; Koirala, Tapendra; Shrestha, Purnima; Mishra, Ujjwal Kumar (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Hand hygiene is the most effective infection prevention measure. This research aims to find out the knowledge and practice of hand hygiene among the doctors of major departments of Patan Hospital.Method: A cross-sectional study was conducted among doctors of selected departments of Patan Hospital, Lalitpur, Nepal. The knowledge of hand hygiene was assessed using a WHO knowledge questionnaire. The practice was assessed using a WHO observation checklist. The data was recorded in Epi-info and the analysis was done for knowledge score and compliance with practice using SPSS v15. A p-value of